Is Phosphoric Acid Connected to Autism: An Hypothesis - Gelbard, Amos (British Journal of Healthcare and Medical Research, 2025)
In this letter to the editor I will present a short hypothesis regarding Phosphoric Acid’s possible role in Autism, in regard to its role in the ATP to ADP cycle and Glutamate to Glutamine cycle. The hypothesis is short and still doesn’t have sufficient basis because of the seldom researched nature of Phosphoric Acid in autism but it explains a logic as to why it could, perhaps, be important and asks for further studying of the subject.